Disordered contact networks in jammed packings of frictionless disks. (9th November 2016) - Ramola, Kabir; Chakraborty, Bulbul
Abstract: We analyse properties of contact networks formed in packings of soft frictionless disks near the unjamming transition. We construct polygonal tilings and triangulations of the contact network that partitions space into convex regions which are either covered or uncovered. This allows us to characterize the local spatial structure of the packing near the transition using well-defined geometric objects. We construct bounds on the number of polygons and triangulation vectors that appear in such packings. We study these networks using simulations of bidispersed disks interacting via a one-sided linear spring potential. We find that several underlying geometric distributions are reproducible and display self averaging properties. We find that the total covered area is a reliable real space parameter that can serve as a substitute for the packing fraction. We find that the unjamming transition occurs at a fraction of covered area A G ∗ = 0.446 ( 1 ) . We determine scaling exponents of the excess covered area as the energy of the system approaches zero E G → 0 +, and the coordination number ⟨ z g ⟩ approaches its isostatic value Δ Z = ⟨ z g ⟩ − ⟨ z g ⟩ i s o → 0 + . We find Δ A G ∼ Δ E G 0.28 ( 1 ) and Δ A G ∼ Δ Z 1.00 ( 1 ), representing new structural critical exponents. We use the distribution functions of local areas to study the underlying geometric disorder in the packings. We find that a finite fraction of order Ψ O ∗ = 0.369 ( 1 ) persists as the transition is approached.